Upgrading lignocellulosic ethanol for caproate production via chain elongation fermentation. (November 2018) - Yang, Peixian; Leng, Ling; Tan, Giin-Yu Amy; Dong, Chengyu; Leu, Shao-Yuan; Chen, Wen-Hsing; Lee, Po-Heng
Abstract: Chain elongation is a promising mixed culture bioprocess to convert acetate into medium chain carboxylates with ethanol as an electron donor. Caproate production using lignocellulosic ethanol (LE) as feedstock via chain elongation fermentation was examined in this study. Meanwhile, the effects of yeast extract and cellulose containing in the LE were investigated separately. Fermentation performance showed that the lag phase of caproate production were shortened in experimental group LE (4 days), yeast extract (6 days), and cellulose (9 days) compared with the control group (17 days) without extra supplement. The insufficiency of electron donor, ethanol, limited further elongation into caproate, resulting in comparable caproate yields and carbon conversion ratios in four experimental groups. Microbial community and microbial kinetics analysis revealed that yeast extract could be metabolized by protein-utilizing bacteria into short chain carboxylates (SCCs), which facilitated biological chain elongation. Meanwhile, yeast extract boosted microbial growth by serving as nitrogen and other nutrient sources. Furthermore, cellulose was utilized and further converted into SCCs, or even caproate, by cellulolytic bacteria. Together, caproate production was enhanced with high microbial activities and intermediates formation using LE. This study upgrades LE into a higher energy density product, caproate, via the energy-efficient chain elongation fermentation. Graphical abstract: Highlights: Lag phase of caproate formation was shortened by 13 d with lignocellulosic ethanol. Insufficiency of ethanol limited further elongation of butyrate into caproate. Lignocellulosic ethanol as feedstock enriched the microbial community. Cellulose and yeast extract shortened the lag phase of caproate production. Yeast extract boosted bacterial growth thus improving fermentation performance.